Combatting the cassava green mite - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Handbook on the cassava green mite (Mononychellus tanajoa) in Africa. A guide to its biology and procedures for implementing classical biological control by J S Yaninek, G J de Moraes and R H Markham 140pp 1989 ISBN 978 131 037 5, IITA, Oyo Road, PM